Bangkit Pascainfeksi: Dinamika Resiliensi pada Penyintas Covid-19 - Yudi Kurniawan; Markus Nanang Irawan Budi Susilo (Faculty of Psychology, Universitas Semarang, 2021)
Abstract. This study aims to qualitatively understand the dynamics of resilience in survivors of COVID-19. Since the Coronavirus Disease (COVID-19) was declared a pandemic by the World Health Organization, the number of people infected has increased. Until April 2021, the number of positive confirmed COVID-19 cases in Indonesia has reached 1.5 million cases. Of these, 1.3 million people became survivors. In many cases, survivors of COVID-19 are still symptomatic for more than 60 days after the first onset appeared. This condition is known as long COVID. In addition to long COVID-19, survivors also face the risk of stigmatization from the environment that is burdensome for patients who have recovered to be able to return to normal activities. This study uses a phenomenological approach. Researchers conducted in-depth interviews with four respondents who had tested positive for COVID-19 based on the results of PCR swabs and experienced several long symptoms of COVID. The researchers found that the dynamics of resilience in COVID-19 survivors in this study emerged as an interaction between protective factors and risk factors. The protective factor consists of the components I can, I have, and I am plus the empathy and spiritual factors. The risk factors experienced by participants in this study were social stigma and the long-term impact of COVID-19. Collaboration between components of adaptive thinking, the ability to manage emotions, social support and empathy and spiritual factors is the key to achieving psychological resilience. Keywords: pandemic, COVID-19 survivors, resilience, long COVID, social stigma Abstrak. Penelitian ini bertujuan untuk memahami secara kualitatif dinamika resiliensi pada penyintas COVID-19. Sejak Coronavirus Disease (COVID-19) ditetapkan sebagai pandemi oleh Organisasi Kesehatan Dunia, jumlah masyarakat yang terinfeksi kian meningkat. Hingga April 2021, jumlah konfirmasi positif COVID-19 di Indonesia mencapai 1,5 juta kasus. Dari jumlah tersebut, 1,3 juta orang menjadi penyintas. Pada banyak kasus, penyintas COVID-19 masih bergejala hingga lebih dari 60 hari setelah onset pertama muncul. Kondisi ini dikenal sebagai long COVID. Selain long COVID, penyintas pun menghadapi risiko stigmatisasi dari lingkungan yang memberatkan pasien yang telah pulih untuk dapat kembali berkegiatan secara normal. Penelitian ini menggunakan pendekatan fenomenologi. Peneliti melakukan wawancara mendalam terhadap empat responden yang pernah dinyatakan positif COVID-19 berdasarkan hasil swab PCR dan mengalami beberapa gejala long COVID. peneliti menemukan bahwa dinamika resiliensi pada penyintas COVID-19 dalam penelitian ini muncul sebagai interaksi antara faktor protektif dan faktor risiko. Faktor protektif terdiri atas komponen I can, I have, dan I am ditambah dengan faktor empati dan spiritual. Faktor risiko yang dialami oleh partisipan dalam penelitian ini adalah stigma sosial dan dampak jangka panjang COVID-19. Kolaborasi antara komponen pola pikir adaptif, kemampuan mengelola emosi, dukungan sosial dan faktor empati serta spiritual merupakan kunci untuk mencapai resiliensi psikologis.Kata kunci: pandemi, penyintas COVID-19, resiliensi, long COVID, stigma sosial